Binge eating as emotion regulation?: A meta-analysis of ecological momentary assessment studies - Borm, Insa; Hartmann, Steffen; Barnow, Sven; Prüßner, Luise (Clinical psychology review, 2025)
Over the past decade, app-based studies have increasingly explored whether binge eating may serve as a form of emotion regulation. While theoretical models consistently propose that binge eating is triggered by aversive states, they diverge on whether the behavior is reinforced by subsequent temporary emotional improvements. This meta-analysis synthesized findings from 59 reports (42 unique studies, 1745 participants, 478 effect sizes) using ecological momentary assessment (EMA) to examine the role of negative and positive emotions in binge eating. Our analysis focused on two aspects: the emotion levels before and after binge eating, quantified using standardized mean change effect sizes, and the temporal emotion trajectories before and after binge eating, analyzed using Fisher's r-to-z transformed correlations. Using robust variance estimation (RVE) to account for dependent effect sizes, random-effects models revealed consistent emotion deterioration before binge eating across analyses, supporting the premise that emotional distress triggers binge eating. However, post-binge emotions yielded mixed results: while emotion levels indicated a continued deterioration, temporal trajectories suggested slight improvements after binge eating. Meta-regressions revealed no significant moderating effects, suggesting unexplained heterogeneity between studies. These findings partially support the emotion regulation function by affirming emotional distress as a trigger for binge eating but challenging the reinforcement premise. Treatments may benefit from incorporating strategies to regulate both negative and positive emotions. Substantial between-study heterogeneity highlights the need for future research to address methodological inconsistencies and refine our understanding of how emotions contribute to binge eating maintenance, which is essential for improving therapeutic outcomes for individuals with eating disorders.